2022
DOI: 10.1177/20406223221076890
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations of long-COVID syndrome: a narrative review

Abstract: Accumulating evidence points toward a very high prevalence of prolonged neurological symptoms among coronavirus disease 2019 (COVID-19) survivors. To date, there are no solidified criteria for ‘long-COVID’ diagnosis. Nevertheless, ‘long-COVID’ is conceptualized as a multi-organ disorder with a wide spectrum of clinical manifestations that may be indicative of underlying pulmonary, cardiovascular, endocrine, hematologic, renal, gastrointestinal, dermatologic, immunological, psychiatric, or neurological disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
170
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(182 citation statements)
references
References 154 publications
(297 reference statements)
7
170
0
5
Order By: Relevance
“…A systematic review and meta-analysis, including data from 47,910 patients, showed that up to 80% of infected patients developed at least one long-lasting symptom, including fatigue (58%), memory loss (16%), anxiety (13%) and depression (12%) [ 13 ]. Another recently published systematic review including 51 studies (n = 18,917 patients) also reported persistent problems with sleep disturbance (27%), anxiety (19%), depression PTSD (16%), and cognitive impairment (20%).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis, including data from 47,910 patients, showed that up to 80% of infected patients developed at least one long-lasting symptom, including fatigue (58%), memory loss (16%), anxiety (13%) and depression (12%) [ 13 ]. Another recently published systematic review including 51 studies (n = 18,917 patients) also reported persistent problems with sleep disturbance (27%), anxiety (19%), depression PTSD (16%), and cognitive impairment (20%).…”
Section: Introductionmentioning
confidence: 99%
“…51 Emering evidence suggests that the clinical manifestations of long COVID may also be characterized by sex differences. 5254 Our results show a cluster with predominantly hospitalized and male patients (cluster 1) and other clusters with predominantly non-hospitalized and female patients (clusters 3 and 4), which suggests that males and females may differ with respect to long COVID manifestations. A focused, prospective study could help to clarify the extent potential sex differences in long COVID.…”
Section: Discussionmentioning
confidence: 64%
“…As also observed in our sample, symptoms correlating to neurological and neuropsychiatric dysfunction are common, including headache, cognitive impairment, smell/taste disorders, sleep and mood disorders, myalgias, and dysautonomia, thereby representing core aspects of the Long COVID Syndrome [ 25 ]. Similarly, summarizing evidence to date, a recently published systematic review and meta-analysis, including data from 47,910 patients, showed that up to 80% of infected patients developed one or more long-lasting neuropsychiatric symptoms, including fatigue (58%), headache (44%), attention disorder (27%), ageusia (23%), anosmia (21%), memory loss (16%), anxiety (13%), and depression (12%) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%